“Efectos comparativo de ácido indol butirico (AIB) y tipos de sustratos en el enraizamiento de ficus (ficus benjamina L.) a través de acodo aéreo en el distrito de morales-San Martín” - Arce Grández, Carlos Mao (2014)
This paper titled "EFFECT COMPARISON OF ACID INDOL BUTYRIC (AIB) ANO TYPES OF SUBSTRATES ON THE ROOTING OF Ficus (Ficus benjamina L.) LAYERING THROUGH AIR IN THE DISTRICT OF MORALES-SAN MARTIN", aimed to determine the comparative effect of índole butyric acid (IBA) and types of media that Works best in the rooting of Ficus benjamina L. in the form of air layering; and evaluating the vegetative development of roots of different treatments studied. This research was conducted in 150 days and was held in the garden of the premises of the Faculty of Agricultura! Sciences in the university town of UNSM-T, located in the district moral of thecity of Tarapoto; Root length, number of roots, ,Volume Root and Percentage of Estate: where four variables as assessed. The substrates used for rooting were: Black earth, Vacaza, Gallinaza, Compost, Vermicompost and washed sand; these substrates were obtained from the area. The experimental design was usedis a design randomized complete block (RCBD) with 6 treatments and 3 blocks. Regarding the study in this research, the best treatment for rooting of Ficus benjamina L. by vegetative propagation method "air layering" is the treatment of black earth, as 1 showed very good results in different variables evaluated. And alternatively propagation through air layering method the three substrates; as well as lndole Butyric acid synthetic hormone (AIB) are suitable to use for propagating Ficus. lt isconcluded that the major vegetative development of roots was obtained from treatments: Black Earth, Gallinaza, lndole Butyric Acid and Compost.